AVM nuclear glass/steel/claystone system altered by Callovo–Oxfordian poral water with and without cement–bentonite grout at 70°C. Issue 3 (28th July 2020) - Carriere, Charly; Neff, Delphine; Martin, Christelle; Tocino, Florent; Delanoë, Alexis; Gin, Stephane; Michau, Nicolas; Linard, Yannick; Dillmann, Philippe
Abstract: The effect of a cement–bentonite grout material was studied through glass/steel interactions. Hence, two experimental mock‐ups, consisting of a "sandwich" of four materials in contact, stainless steel/AVM glass/AVM glass/P285NH steel, were leached by Callovo–Oxfordian poral water at 70°C for 1 year. CBG material was added for one experiment, whereas the second one was CBG‐free. Chemical and structural analyses (scanning electron microscopy–energy‐dispersive X‐ray spectroscopy, Raman), performed mainly at the AVM glass/P285NH interface, evidenced a comparable alteration with and without the CBG. Indeed, its presence did not impact the gel formation by hydrolysis/condensation mechanism. For both experiments, the glass alteration rates corresponded to r 0 Cox, 70 ° C / 32, highlighting a kinetic rate drop after a 1‐year leaching period. However, the CBG impacted the pH solution initially buffered by the claystone, promoting precipitation of Mg/Fe‐rich silicates on the gel surface. Regarding P285NH corrosion, no major difference was observed with the CBG. Steel corrosion layers in both experiments were Si‐free, and the corrosion rates were similar. Therefore, after 1 year at 70°C, the CBG had a limited effect on the glass/carbon steel interactions. Abstract : The effect of a cement–bentonite grout material was studied through glass/steel interactions. Experimental mock‐ups with four materials in contact, stainless steel/AVM glass/AVM glass/P285NH steel, were leached by Callovo–Oxfordian poral water at 70°C for 1 year—one with added CBG and one CBG‐free. Chemical and structural analyses evidenced a comparable alteration with and without the CBG.